'Art Lift' intervention to improve mental well‐being: An observational study from UK general practice. (16th August 2012) - Crone, Diane M.; O'Connell, Elaine E.; Tyson, Phillip J.; Clark‐Stone, Frances; Opher, Simon; James, David V. B.
Abstract: Arts for health interventions are emerging as an alternative option to medical management of mental health problems and well‐being. This study investigated process and outcomes of an art intervention on patients referred by primary care professionals, including associations between patient characteristics (e.g. sex), progress through the intervention (e.g. attendance), and changes in mental well‐being. Referral criteria included people with anxiety, depression, or stress; low self‐esteem, confidence, or overall well‐being; and chronic illness or pain. The study took place in UK‐based general practitioner practices, with a total of 202 patients referred to a 10‐week intervention. Patient sociodemographic information was recorded at baseline, and patient progress assessed throughout the intervention. Significant improvement in well‐being was revealed for the 7‐item (t = −6.049, d.f. = 83, P < 0.001, two‐tailed) and 14‐item (t = −6.961, d.f. = 83, P < 0.001, two‐tailed) scales. Of referred patients, 77.7% attended and 49.5% completed. Most patients were female, and from a range of socioeconomic groups, and those who completed were significantly older (t = −2.258, d.f. = 145, P = 0.025, two‐tailed). Findings reveal that this art intervention was effective in the promotion of well‐being and in targeting women, older people, and people from lower socioeconomic groups.